Action observation improves sit-to-walk in patients with Parkinson's disease and freezing of gait. Biomechanical analysis of performance. (November 2020) - Mezzarobba, Susanna; Grassi, Michele; Pellegrini, Lorella; Catalan, Mauro; Krüger, Björn; Stragapede, Lara; Manganotti, Paolo; Bernardis, Paolo
Abstract: Introduction: Freezing of gait (FoG) is one of the most disabling gait disorders in Parkinson's disease (PD), reflecting motor and cognitive impairments, mainly related to dopamine deficiency. Recent studies investigating kinematic and kinetic factors affecting gait in these patients showed a postural instability characterized by disturbed weight-shifting, inappropriate anticipatory postural adjustment, worse reactive postural control, and a difficulty executing complex motor tasks (i.e. sit-to-walk). These symptoms are difficult to alleviate and not very responsive to Levodopa. For this reason, additional therapeutic actions based on specific therapeutic protocols may help patients with their daily lives. We conducted a randomized control trial aimed to test if two clinical protocols for PD patients with FoG were effective to improve postural control. Methods: Rehabilitation protocols, conceived to improve gait, were based on learning motor exercises with the Action Observation plus Sonification (AOS) technique, or by the use of external sensory cues. We collected biomechanical data (Center of Mass COM, Center of Pressure COP, and moving timings), using the sit-to-walk task as a measure of motor and gait performance. Results: Kinetic and kinematic data showed that when treatment effects consolidate, patients treated with AOS protocol are more efficient in merging subsequent motor tasks (sit-to-stand and gait initiation), and diminished the total moving time and the area of the COP positions. Conclusion: We demonstrated for the first time that PD patients with FoG treated with an AOS protocol aimed at relearning appropriate gait patterns increased balance control and re-acquired more efficient postural control. Highlights: PD with FoG show postural instability and difficulty executing complex motor tasks. Therapeutic actions based on specific cognitive protocols help to alleviate symptoms. Evaluation of protocols results lack investigations into biomechanical parameters. Short-term rehabilitation protocols improve postural control and total execution time. Biomechanical data showed that AO protocol eases merging of subsequent motor tasks.